ONLINE LEARNING TOWARDS ECONOMIC STUDENTS A CASE STUDY: EFFECTIVENESS VS PSYCHOLOGICAL IMPACT - Farizal Khusnul; Agus Tohawi (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2021)
This purpose of conveying this study is to determine the effectiveness of onlinelearning and its psychological impact. This article is trying to look at the learning activity thatutilized by students and their interaction pattern during remote to the online learning. Thisresearch applied a qualitative with a case study approach, the data were carried out byobservation, interviews, and documentation. The data were analyzed descriptively usingMiles and Huberman analysis model, namely data condensation, data presentation, anddrawing conclusions, and testing the validity of the data using triangulation as a way toincrease the degree of trust in the research conducted. The research results showed that thereare several factors that influence the effectiveness of this online learning, such as a). Lowmastery of technology, b). Lack of infrastructure suggestions, c). Lectures delivered are lessthan optimal, d). Educators / lecturers are required to be proficient in using online learningtechnology. Meanwhile, some of the factors above have a psychological impact on manystudents who complain caused of limited infrastructure and lack of readiness and experience,as well as the number of assignments given with a short time, so students tend to be stresscaused by several of the factors above. Moreover, in general online learning is consideredless effective. However, in the midst of the COVID-19 pandemic, this policy is a goodstrategy to break the chain of the virus.